The impact of sex segregation by economic activity on the gender pay gap across Europe - Petroula M. Mavrikiou; Julijana Angelovska (UTMS Journal of Economics, 2020)
The gender pay gap is a complex issue caused by a number of interrelated factors and has inevitable impact on the status of women in their economic and social life. The objectives of this paper are concentrated in investigating the sex-segregation by economic activity in the labour market and its relationship to the gender pay gap across Europe. Dissimilarity index is calculated and sectoral gender based segregation in EU during 2010 was on average 0.30, meaning that 30% of the employed population would need to change economic activity in order to have an equal distribution of men and women. The findings of cluster analysis showed the paradox that some countries like Luxemburg, Belgium, Poland have high dissimilarity indices and lowest percentage of gender pay gap or Scandinavian with the highest dissimilarity indices have gender pay gap around the mean on the European level.
Keywords: J16; J31; N30; 330; gender inequality; dissimilarity index; cluster analysis; horizontal sex-segregation; labor market